Toroidal Dipolar Response in Metamaterials Composed of Metal–Dielectric–Metal Sandwich Magnetic Resonators - Chaojun Tang; Jing Chen; Qiugu Wang; Zhendong Yan; Bo Liu; Fanxin Liu; Chenghua Sui (IEEE Photonics Journal, 2016)
Toroidal metamaterials have been drawing increasing interest recently because of their unusual electromagnetic properties and a variety of potential applications. In this work, we have investigated numerically toroidal dipolar response at optical frequency in metamaterials whose unit cell includes three magnetic resonators. The magnetic resonators are metal–dielectric–metal sandwich nanostructures, which are composed of two Ag rods and a SiO 2 spacer. They have the same shape and dimension, but they are placed at different positions to break the space-inversion symmetry. The near-field plasmon coupling between magnetic resonators leads to the excitation of a toroidal dipolar mode, which is characterized by a head-to-tail distribution of magnetic dipoles within magnetic resonators. In our designed toroidal metamaterials, space-inversion symmetry breaking is needed only in the polarization direction of incident light, and light can be normally incident on the toroidal metamaterials.